The Lay-up Number on Ultraviolet Resistant Properties of Polyester/Nylon Composite Microfiber Artificial Leather - Shaoni MENG; Caiqian ZHANG; Peirong BO (Pige Kexue Yu Gongcheng)
The summer clothing of polyester/nylon composite microfiber artificial leather has the characteristics of air permeability, heat dissipation and UV protection, among which the anti-UV performance is the focus to consumers. To study the UV resistance differences of polyester/nylon composite microfiber artificial leather, several samples were selected to test the UV resistance under the superposition of 1, 2, and 3 layers. The results show that two and three layers of fabrics can meet the standard requirements of anti-ultraviolet. Specifically, the polyester/nylon composite microfiber artificial leather with higher warp and weft density has a good UV resistance. The deviation of Ultraviolet A (UVA) transmittance decreases with the increase of the layer number, while the coefficient of variation (CV) of Ultraviolet Protection Factor (UPF) does not decrease. There is a negative linear correlation between UVA transmittance and total density and a positive linear correlation between UPF and the product of total density and compactness.